Predictors of spiritual struggles: an exploratory study - Ano, Gene. G. (Mental health, religion & culture, 2013)
The purpose of the current study was to identify factors that predict spiritual struggles. It was hypothesised that factors from religious (e.g., God image, attachment to God, church attitudes, religious history), personal (e.g., neuroticism, pessimism, trait anger), social (e.g., social support, loneliness), and situational (e.g., negative appraisals) domains may predispose people to spiritual struggles during times of distress. Participants (309 undergraduate students) filled out questionnaires measuring relevant constructs and a two-step hierarchical multiple regression equation was generated separately for each of the four domains. Upon identifying significant predictors from each of the four domains, a final hierarchical regression equation revealed that: (1) more negative appraisals of a stressful situation, (2) an insecure ambivalent attachment to God, and (3) neuroticism significantly predicted unique variance in spiritual struggles beyond the effects of relevant religious variables, thus generally supporting the hypothesis that spiritual struggles are complex phenomena that stem from multiple factors.